Indigenous media producers' perspectives on objectivity, balancing community responsibilities and journalistic obligations. (November 2018) - Burrows, Elizabeth
Professional communicators produce a diverse range of global Indigenous media while balancing professional journalistic conventions such as 'objectivity' against community and organizational responsibilities. Despite their work being tarred as biased, soft or preaching to the converted, Indigenous media producers argue that their work counterbalances biased mainstream media coverage that hampers Indigenous public sphere participation and denigrates Indigenous communities and individuals. Through interviews with 42 Indigenous media producers from Australia, Canada, Finland, Sweden and New Zealand, this study investigates their journalistic processes and attitudes to professional norms such as objectivity, source choices and news values. The article interrogates how Indigenous media producers navigate the tensions between their professional obligations and community responsibilities. It argues Indigenous media producers apply a modified version of objectivity to produce fact-driven content that promotes Indigenous perspectives, prioritizes Indigenous voices and serves the needs of their communities.